From invisible to SEEN: a conceptual framework for identifying, developing and evidencing unassessed graduate attributes. Issue 7 (10th November 2018) - Kensington-Miller, Barbara; Knewstubb, Bernadette; Longley, Alys; Gilbert, Amanda
ABSTRACT: Academic transcripts record students' learning, providing a grade which indicates the student has achieved a certified level of disciplinary knowledge and skill. However, recognising what a graduate has accomplished during a course, or over a programme is much more involved: it includes not only disciplinary awareness but students' learning processes (e.g., autonomous learning), social aptitude (e.g., diversity awareness and collaborative skills), and even their professional readiness (e.g., time-management and resilience). Such learning is often invisible on university academic rubrics and transcripts, and may be difficult for students to articulate and evidence to others. In this article, we introduce the concept of 'invisible' graduate attributes at the tertiary level, distinguishing such unassessed/unassessable attributes from more visible graduate attributes. We then introduce our conceptual framework, SEEN, for articulating, evidencing and actively developing 'invisible' attributes. We argue that the SEEN framework provides the basis for a toolkit for students, lecturers and employers.